Distal root hemisection of mandibular left first molar with pulp necrosis, bifurcation perforation, and symptomatic apical periodontitis - Regina, APrima Vista Okta; Maharani, Cyntia Dewi; Widyastuti, Andina; Rinastiti, Margareta (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Hemisection is an endodontic surgery performed by removing one or more roots and existing crown structures to increase the retention of the remaining teeth and to correct defected dental roots that are not possible to maintain. This defect can be caused by pulp tissue or periodontal tissue. Diagnosis of endodontic-periodontal lesions is an essential determinant whether it is due to endodontic or periodontal pathogens. In this case, endodontic treatment needs to be performed in combination with hemisection surgery. The purpose of this case report is to save the tooth with furcation involvement and pulp necrosis, making it perforated on the bifurcation of mandibular first molar. A female patient aged 20 years had a large cavity in tooth 36 with symptomatic apical periodontitis. The tooth was sensitive to percussion test and negative to palpation test, and the mobility was normal. The radiographic feature showed a perforated tooth in the furcation section and furcation involvement. The diagnosis of tooth 36 was pulp necrosis with bifurcation perforation and symptomatic apical periodontitis. The patient received initial treatment, root canal treatment, and obturation on the mesial first molar, then followed by intake of the distal root of the molar. The installation of a prefabricated fiber post in the mesial root of tooth 36 and hemisection surgery were performed on tooth 36. The restoration was done in the form of a full porcelain fused to metal crown on tooth 36 with a splinted crown. Hemisection surgical treatment is a reliable alternative solution and has a good prognosis because it can maintain dental and periodontal tissue as long as possible without tooth extraction.